ULTRASTRUCTURAL CHANGES OF THE AERO-HEMATIC BARRIER COMPONENTS OF THE RESPIRATORY PORTION OF THE LUNGS IN THE DYNAMICS AFTER EXPERIMENTAL THERMAL TRAUMA AND USAGE OF THE LYOPHILIZED XENOGRAFT - Небесна, З.М.; К. С. Волков. А. О. Котик; Kotyk A. O. (World of Medicine and Biology, 2014)
In the experiment on white rats the condition of submicroscopic components of the aero-hematic barrier of the respiratory portion of the lung was studied in the early and late stages of toxemia, septicotoxemia after thermal trauma in terms of early necrectomy and usage morselized substrate of lyophilized xenograft. Established that the use xenograft prevents development of destructive changes in the structures of the aero-hematic barrier in the early stages of the experiment and a positive effect of regenerative processes and their normalization in the later stages of the experiment.